Naucline, a new indole alkaloid from the bark of nauclea officinalis - Liew, Sook Yee; Mukhtar, M. R.; Hadi, A. H. A.; Awang, Khalijah; Mustafa, Mohd Rais; Zaima, K.; Morita, H.; Litaudon, M. (MDPI, 2012)
A new indole alkaloid, naucline (1) together with four known alkaloids, angustine (2), angustidine (3), nauclefine (4) and naucletine (5), were isolated from the bark of Nauclea officinalis. The structures of all isolated compounds were elucidated with various spectroscopic methods such as 1D- and 2D- NMR, IR, UV and LCMS-IT-TOF. In addition to that of alkaloid 1, the complete 13C-NMR data of naucletine (5) were also reported. Naucline (1) showed a moderate vasorelaxant activity (90 relaxation at 1 Ã 10â5 M) whereas, angustine (2), nauclefine (4), and naucletine (5) showed potent vasorelaxant activity (more than 90 relaxation at 1 Ã 10â5 M) on an isolated rat aorta.